(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: In Khanh Vinh district, Khanh Hoa province, the number of malaria cases increased markedly during the period 2021–2024, indicating a persistent risk of malaria outbreaks. In this context, assessment of community-level malaria immune responses is of great importance, as it reflects the extent of exposure to malaria parasites and supports the development of appropriate prevention and control strategies. Objectives: Determine the proportion of residents with anti-malarial antibodies using the ELISA method and identify associated factors in the study area. Methods: A cross-sectional descriptive study was conducted in Tay Khanh Vinh and Nam Khanh Vinh communes, Khanh Hoa province, in August 2025. A total of 1,364 residents were enrolled, and serum samples were collected and tested for anti-malarial antibodies using ELISA. Results: Among 1,364 serum samples tested, 544 were positive for anti-malarial antibodies, corresponding to a seroprevalence of 39.9%. The ELISA positivity rate was similar between males (40.2%) and females (39.7%). The lowest seroprevalence was observed in participants under 15 years of age (7.9%) and increased progressively in those aged 15–29 years (39.4%), 30–44 years (52.7%), and was highest among individuals aged over 45 years (71%). Participants with a history of malaria infection had a significantly higher ELISA positivity rate (68%) compared with those without a history of malaria (35.8%). Conclusions: The prevalence of antibodies against Plasmodium spp. in the study population remains relatively high (39.9%), highlighting the need for strengthened health communication and malaria prevention and control interventions targeting high-risk groups in the community.